Application of an alternative mesh morphing method on the numerical modeling of oscillating wave surge converters - Vargas,Guilherme Fuhrmeister (2019)
ABSTRACT A technology capable of converting the horizontal motion of the ocean waves into energy by the application of a flap-piston system has been improved over the last few years, this device is known as oscillating wave surge converter. This system has great potential, already proven, for electric power generation. The computational fluid dynamics is one of the most used tools for the study of wave energy converters. In this context, the present paper proposes the application of an alternative mesh morphing method to represent the hydrodynamics of these devices, which is based on a bottom that oscillates with the converter, leading the flap to reach high inclinations without causing numerical divergences. The study is performed using the OpenFOAM computational code and its extension OLAFOAM. These are based on Reynolds Average Navier Stokes (RANS) turbulence modeling and the Volume of Fluid method (VOF) for the free surface representation, which are applied to a bidimensional model, allowing the numerical modeling of the converter. The proposed method presented good agreement of the results when compared to the experimental studies in similar hydrodynamic cases. The methodology based on a moving bottom presented relative differences, concerning the method that considers the bottom as fixed, between 4% and 17% for the cases where the flap is near to the ocean bottom and up to 8% for cases where it is further away.